Peran Lembaga Internasional dalam Menjamin Akses Obat Esensial: Peluang dan Tantangan di Negara Berkembang - Sari, Septi Purnama; Hidayatullah, Yusuf; Febrianti, Siska; Mery (Program Studi Farmasi Sekolah Tinggi Ilmu Kesehatan Sambas, 2025)
Access to essential medicines is a critical component in ensuring the right to health, yet it remains a major challenge in developing countries. Economic disparities, patent monopolies, fragile supply chains, and inadequate distribution infrastructure have left large populations without access to safe, effective, and affordable treatment. This study aims to analyze the strategic roles of international organizations such as WHO, UNICEF, and Gavi, in expanding access to essential medicines, while also identifying associated opportunities and challenges. A systematic literature review was conducted using peer-reviewed journals, official reports, and current policy documents. The findings indicate that WHO contributes through global standard setting and drug prequalification; UNICEF focuses on vaccine procurement and distribution; and Gavi drives innovative financing and global partnerships. Nevertheless, significant challenges persist, including intellectual property constraints, dependence on imported raw materials, circulation of falsified drugs, and sustainability issues in post-donor settings. Strategic opportunities include cross-agency collaboration, digital technology adoption, and strengthening of local production capacity. This study underscores the importance of aligning national policies with international support to develop an equitable and sustainable pharmaceutical system. Access to essential medicines must be recognized as a shared global responsibility within the framework of human rights and global solidarity.